Effects of the association between spirituality, religiosity and physical activity on health/mental health: a systematic review - Moreira, Wanderson Carneiro; Nóbrega, Maria do Perpétuo Socorro de Sousa; Lima, Fernanda Púpio Silva; Lago, Eliana Campêlo; Lima, Mário Oliveira (Revista da Escola de Enfermagem da USP, 2020)
Objective: To identify evidence in the literature about the effects of the association between spirituality, religiosity and physical activity on physical and mental health. Method: A systematic review conducted in January 2019 in the MEDLINE/PubMed, SCOPUS, Web Of Science, CINAHL, PsycINFO, LILACS and SciELO databases with the descriptors: “spirituality”, “religion”, “physical activity” and “physical exercise ”. Primary studies carried out with adults published until 2018 in Portuguese, English or Spanish were included. Results: Nine international studies were selected which had been published between 2011 and 2017, with cross-sectional design (55%) and an evidence level of four (78%). Eight studies addressed effects on physical health and one addressed effects on mental health. Conclusion: The association between spirituality, religiosity and physical activity promotes effects on physical and mental health, however the available evidence is not sufficient for this association to be applied in clinical practice.